Thrombosis of mechanical mitral valve prosthesis during pregnancy: An ongoing “saga” in need of comprehensive solutions - Mahgoub, Ahmed (Glob Cardiol Sci Pract, 2020)
Emergency treatment for thrombosed mechanical valve prothesis during pregnancy is not uncommon in low- and middle-income countries. The presence of a mechanical valve continues to be an important cause of maternal morbidity and mortality. There is a pressing need for increasing awareness and feasible solutions for this huge problem. We here describe four patients who needed emergency treatment for thrombosis of mechanical valve prothesis during pregnancy and review the evolving comprehensive strategies for dealing with this issue.